2010
DOI: 10.1186/1471-2164-11-304
|View full text |Cite
|
Sign up to set email alerts
|

A critical assessment of cross-species detection of gene duplicates using comparative genomic hybridization

Abstract: BackgroundComparison of genomic DNA among closely related strains or species is a powerful approach for identifying variation in evolutionary processes. One potent source of genomic variation is gene duplication, which is prevalent among individuals and species. Array comparative genomic hybridization (aCGH) has been successfully utilized to detect this variation among lineages. Here, beyond the demonstration that gene duplicates among species can be quantified with aCGH, we consider the effect of sequence div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Machado and Renn (Machado and Renn 2010) suggested gene duplication as an important source of functional novelty, as it has been shown to be involved in adaptive evolution in response to diet (Zhang et al 2002), chemical challenge (Labbé et al 2007), and reproductive incompatibility (Lynch and Force 2000). Our GO analyses indeed showed duplications for genes involved in both abiotic and biotic stress responses (see Supplemental Figures 2C and 2D online), potentially providing the genetic variability to rapidly respond to environmental factors in both sexual and apomictic forms.…”
Section: Cnv As An Adaptive Mechanism In Apomictic Boecheramentioning
confidence: 59%
“…Machado and Renn (Machado and Renn 2010) suggested gene duplication as an important source of functional novelty, as it has been shown to be involved in adaptive evolution in response to diet (Zhang et al 2002), chemical challenge (Labbé et al 2007), and reproductive incompatibility (Lynch and Force 2000). Our GO analyses indeed showed duplications for genes involved in both abiotic and biotic stress responses (see Supplemental Figures 2C and 2D online), potentially providing the genetic variability to rapidly respond to environmental factors in both sexual and apomictic forms.…”
Section: Cnv As An Adaptive Mechanism In Apomictic Boecheramentioning
confidence: 59%
“…We employed a novel approach to correct this bias by using a signal adjustment strategy, which - unlike previous methods [42, 43] — accounts for sequence mismatches through a global adjustment of cross-species hybridization signal intensities. In brief, we implemented a two-step normalization scheme (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…detected) c EE-AEE-AEE-AEE-APresent manuscript217121210.312.299.599.65.35.3Darby et al 2011 d 9491088.58.299.599.61.31.1Machado et al 2010 e 298755.95.199.599.62.92.1

a A. lyrata genes sharing ≥ 95% sequence identity with their closest A. thaliana homologue [68] are termed highly conserved (compare Additional file 7)

b Headers of half-columns refer to total number of CNEs predicted by Ensembl Plants (E; Vilella et al 2009) alone or additionally by A. lyrata genome analysis (E-A; Hu et al 2011), respectively, as given in parentheses here. Shown are commonalities with these two groups of genes (same column, below) or data referring to these two groups of genes (columns to the right) c True positive is a CNE detected based on array-CGH that was previously predicted to be a CNE by Ensembl Plants [68] alone, or additionally by A. lyrata genome [35] analysis d [42] e [43]

…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high quality of the 3 completed genomes and 11 draft genomes used in our analyses, we were able to combine sequence comparisons and syntenic relationships to determine gene orthologs and observed that, compared to NAP1 references, the members of the NAP7-NAP8 group displayed a higher level of genetic diversity, with an average of 97% identity. We believe that in comparative genome hybridization (CGH) studies, for example, where probe mismatches can affect hybridization (41,49) and where NAP1 or strain 630 genomes have been used as the reference, even a very low number of mismatches between the probe and target DNA can increase the false-negative rate (34,58). This leads us to suggest that the C. difficile CGH arrays, which were designed using either strain 630 (R group) or NAP1 isolate QCD-32g58, may produce numerous falsenegative hybridizations when tested using more a more distantly related strain (e.g., NAP7) and have resulted in the calculation of a smaller core genome size.…”
Section: Discussionmentioning
confidence: 99%